Determining the optimal length of regulatory guarantee: a length‐of‐contract auction - Greve, T.; Pollitt, M. G. (Economic Journal, 2017)
We present an auction design to be used in the area of procurement that allows the length of the regulatory funding period to be determined via an auction. It allows bidders to submit bids against a payment for periods of varying lengths, say 25 and 30 years, instead of a fixed 20‐year contract. This can be desirable for securing more favourable terms in financial markets. It yields efficiency and delivers the optimal length of contract, defined as where social value is maximised. The auction is applicable to any infrastructure investment such as energy, transportation or any area that uses contracts.